2020
DOI: 10.1021/acs.iecr.0c03980
|View full text |Cite
|
Sign up to set email alerts
|

Chloroaluminate Liquid Clathrates: Is It the Cations or the Anions That Drive the Solubility of Aromatics?

Abstract: Three chloroaluminate ionic liquids (ILs), triethyl­ammonium tetrachloroaluminate ([HN222]­[AlCl4]), triethyl­ammonium heptachlorodialuminate ([HN222]­[Al2Cl7]), and tetraethyl­ammonium heptachlorodialuminate ([N2222]­[Al2Cl7]), were employed to investigate liquid clathrate (LC) formation and the relative role of the cation or anion in aromatic solubility. The trend in molar solubilities in all three ILs was found to be benzene > toluene > o-xylene > p-xylene ∼ m-xylene > mesitylene; however, the solubilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These numbers are similar to those recently determined for aromatics in alkylammonium chloroaluminates. 34 As with toluene, the ions of all hydrocarbon-IL mixtures are in close proximity to an abundant hydrocarbon phase, albeit to varying degrees: ethylbenzene and m-xylene (6-7); toluene, o-xylene, napthalene, bromobenzene, and cyanobenzene (12)(13)(14); p-xylene and hexa-uorobenzene (24-26). These differences may arise from differences in channel width or local curvature at the subphase interface, though this was not apparent from visual inspection of the trajectories.…”
Section: Common Neighbour Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers are similar to those recently determined for aromatics in alkylammonium chloroaluminates. 34 As with toluene, the ions of all hydrocarbon-IL mixtures are in close proximity to an abundant hydrocarbon phase, albeit to varying degrees: ethylbenzene and m-xylene (6-7); toluene, o-xylene, napthalene, bromobenzene, and cyanobenzene (12)(13)(14); p-xylene and hexa-uorobenzene (24-26). These differences may arise from differences in channel width or local curvature at the subphase interface, though this was not apparent from visual inspection of the trajectories.…”
Section: Common Neighbour Analysismentioning
confidence: 99%
“…[29][30][31] Interestingly, it is found that formation depends on the strength of the cation-anion interaction and that aromatic solubility is inversely proportional to this strength. [32][33][34] Additionally, interactions with the nonpolar domain of an IL are also likely to play a role 23 since aromatic hydrocarbons are shown to be soluble in non-aromatic ILs. 35,36 Likely each of these factors plays a role to some degree, however until a clearer picture emerges of the molecular interactions leading to this phenomena, it remains difficult to tune the structure for optimal control over separation.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of p -xylene was higher than that of m -xylene in TBAB/EG (1:4) and TBAB/TEG (1:4), but the relationship between the magnitude of the solubility of the two isomers was reversed in TBAB/DEG (1:4). It has been reported , that this o -xylene > p -xylene ∼ m -xylene solubility law is also present in ionic liquids and is likely caused by the effect of the differences in the dipole moments. In addition, the solubility of the HBDs increased with increasing chain length.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility of o -xylene increased faster than the other two isomers and was higher than that of the other two isomers. This phenomenon was attributed to the differences in the induced dipole moment, which is related to the molecular structure. Thus, the structure of the HBAs affected the solubility of the three isomers.…”
Section: Resultsmentioning
confidence: 99%
“…The ILs [HN 222 ]­[Al 2 Cl 7 ] and [HN 222 ]­[AlCl 4 ] were prepared by following our previously reported procedures. , Both were prepared by reacting solid [HN 222 ]Cl (20 mmol, 2.76 g) with solid anhydrous AlCl 3 (20 mmol (2.67 g) or 40 mmol (5.34 g)) at a 1:1 or 1:2 molar ratio under an Ar atmosphere, to produce the colorless solid [HN 222 ]­[AlCl 4 ] and liquid [HN 222 ]­[Al 2 Cl 7 ].…”
Section: Methodsmentioning
confidence: 99%